Piezo-electrocatalytic oxidation of methanol with UV-ozone treated wurtzite zinc oxide nanostructures. (May 2023) - Liu, Nianzu; Wang, Ruoxing; Gao, Shengjie; Zhang, Ruifang; Fan, Fengru; Ma, Yihui; Luo, Xiliang; Ding, Dong; Wu, Wenzhuo
Abstract: Leveraging mechanically-induced piezoelectric polarization, piezocatalysis emerges as a viable mechanism for enhancing the efficiency of catalytic processes. Nanostructured, catalytically active, rationally designed piezoelectric semiconductors can achieve high-performance catalysts for various applications using cost-effective electrocatalytic pathways, such as mechanical stimuli. Here, we design and demonstrate for the first time a cost-effective, high-performance piezo-electrocatalyst for anodic methanol oxidation, which is crucial for the practical application and deployment of direct methanol fuel cells in a variety of emerging clean energy technologies. We synthesized wurtzite ZnO nanorods and nanosheets treated with UV-O3 to characterize and compare their efficacy for piezo-electrocatalytic methanol oxidation. The generation of piezoelectric polarization charges in nanostructured semiconducting ZnO catalysts significantly increased their electrocatalytic performance. By elucidating the charge transfer between mechanically-deformed ZnO nanostructures and methanol molecules, we identified the underlying mechanism for the piezo-electrocatalytic process for methanol oxidation. The facile synthesis of high-quality ZnO nanostructures enables low-cost, scalable manufacture and direct integration into electrocatalysts whose performance could be enhanced by harvesting mechanical energy that would otherwise be wasted in the working environment. Graphical Abstract: A high-performance piezo-electrocatalyst for anodic methanol oxidation was demonstrated and investigated by elucidating the charge transfer between mechanically deformed ZnO nanostructures and methanol molecules. ga1 Highlights: A cost-effective, high-performance piezo-electrocatalyst for anodic methanol oxidation was demonstrated. The efficacy for piezo-electrocatalytic methanol oxidation were characterized for wurtzite ZnO nanorods and nanosheets. The underlying mechanism for the piezo-electrocatalytic process for methanol oxidation was identified.